A mixed-method pilot study to improve patient satisfaction in rural Uganda. Issue 5 (4th July 2018) - Warren, Emily; Nankya, Ethel; Seeley, Janet; Nakamanya, Sarah; Asiki, Gershim; Simms, Victoria; Karabarinde, Alex; Larson, Heidi
ABSTRACT: This article reports on a mixed-method longitudinal field study that was conducted using a tablet-based app capturing data on patients' satisfaction with an outpatient clinic in Kalungu District, Uganda. The app was developed, piloted, and refined using clinician and patient feedback. Findings were reported and discussed in staff meetings, with change in reported levels of satisfaction assessed using descriptive statistical analysis and Chi 2 tests. Qualitative data were collected. Satisfaction was relatively high at baseline and increased by 4.4%, and staff found the feedback actionable. Patients reported fewer delays and better treatment after introducing the app, with the proportion of "very dissatisfied" patients decreasing from 2.3% to zero after six weeks.